2020
DOI: 10.1007/s10668-020-01005-4
|View full text |Cite|
|
Sign up to set email alerts
|

Livelihood diversification as key to long-term non-migration: evidence from coastal Bangladesh

Abstract: Understanding how livelihood diversification contributes to long-term non-migration decisions of people at risks is innovative and timely in the context of future climate change adaptation planning. This study particularly examines this question and explores how and to what extent livelihood diversification in the face of climate change can support long-term non-migration for people living in the southwest coastal region of Bangladesh. We employed a cluster random sampling method to select the respondents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…Again, these voluntary non-migrants appeared to avail significant advantages of accessing to natural resources for their food (𝜒 2 (4) = 14.38;p < 0.01) , fuel collection (𝜒 2 (4) = 12.64;p < 0.01) , timber collection from nearby mangrove forest the Sundarbans (𝜒 2 (4) = 15.51;p < 0.004) , and fishing purpose (𝜒 2 (4) = 21.38;p < 0.000) . These findings are in line with the study findings by Bhusal and Kimengsi (2019), Schewel (2020), and Biswas and Mallick (2020).…”
Section: Community-level Support and Access To Natural Resources Aspectssupporting
confidence: 93%
See 2 more Smart Citations
“…Again, these voluntary non-migrants appeared to avail significant advantages of accessing to natural resources for their food (𝜒 2 (4) = 14.38;p < 0.01) , fuel collection (𝜒 2 (4) = 12.64;p < 0.01) , timber collection from nearby mangrove forest the Sundarbans (𝜒 2 (4) = 15.51;p < 0.004) , and fishing purpose (𝜒 2 (4) = 21.38;p < 0.000) . These findings are in line with the study findings by Bhusal and Kimengsi (2019), Schewel (2020), and Biswas and Mallick (2020).…”
Section: Community-level Support and Access To Natural Resources Aspectssupporting
confidence: 93%
“…Migration is a notable adaptation strategy to cope with risks (including climate risks) and help them diversify their livelihood options (Mallick and Schanze 2020). However, Biswas and Mallick (2020) also suggested that migration is not necessarily compulsory for all affected people. When people have sufficient capital to diversify their livelihood strategies and ensure their well-being even in the face of climatic risks, they may opt to stay at their concerned localities.…”
Section: Conceptual Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human migration is a complex behavioural decision shaped by social, economic, demographic, and ecological conditions of the environment within which an individual inhabits (Hunter et al 2015;McLeman 2018). While not all migration is the result of a strategic choice, the decision to migrate can be considered an adaptive strategy similar to livelihood diversification in the context of adverse environmental conditions or risks (Massey et al 1998;de Haas 2010;Renaud et al 2011;Biswas and Mallick 2020). The migration-adaptation discourse (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to considering the two aspects of non-agricultural employment and agriculture, some scholars have considered the actual situation of farmers' employment, studied the planting industry and breeding industry separately, and made a more detailed classification of farmers' livelihood in the farming-pastoral ecotone (Meng et al, 2013;Dao, 2014;Yang and Xu, 2016). By summarizing the relevant research results, we found that the main characteristics of farmers' livelihood strategies are related to regional differences, the diversity of means and needs, and differences in the conditions of the farmers themselves (Viswanathan and Shivakoti, 2008;Biswas and Mallick, 2021;Hernández-Núñez et al, 2022). Farmers' livelihood choices are closely related to the level of regional economic and social development (Su and Yin, 2020).…”
Section: The Main Features Of the Transformation Of Farmers' Livelihoodmentioning
confidence: 95%